2020
DOI: 10.1108/jfc-08-2019-0113
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported income data: are people telling the truth?

Abstract: Purpose This paper aims to detect anomalous data in income reports of Argentina, including personal income – from a sample of households – and statements of public officials. Design/methodology/approach A widely known technique in forensic accounting – such as Benford’s Law – is used. The Chi-square test and the absolute mean deviation are used for verification. The databases consulted include the income declared by households in the Permanent Household Survey – for the 2003-2017 period – and the capital dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
1
9
0
1
Order By: Relevance
“…The hypothesis which states that there are indications of fraud at PII Corporation according to Benford's Law is rejected. This is in line with previous results (González, 2020;Kruger & Yadavalli, 2017;Kuruppu, 2019;Qin et al, 2019;Striga & Podobnik, 2018). Meanwhile, 3 tests have shown that some data are not in line with Benford's Law distribution, also corroborated by previous research (Alali & Romero, 2013;Davydov & Swidler, 2017;Geyer & Drechsler, 2014;Silva, 2016;Slijepcevic & Blaskovic, 2014).…”
Section: Resultssupporting
confidence: 91%
“…The hypothesis which states that there are indications of fraud at PII Corporation according to Benford's Law is rejected. This is in line with previous results (González, 2020;Kruger & Yadavalli, 2017;Kuruppu, 2019;Qin et al, 2019;Striga & Podobnik, 2018). Meanwhile, 3 tests have shown that some data are not in line with Benford's Law distribution, also corroborated by previous research (Alali & Romero, 2013;Davydov & Swidler, 2017;Geyer & Drechsler, 2014;Silva, 2016;Slijepcevic & Blaskovic, 2014).…”
Section: Resultssupporting
confidence: 91%
“…Notable instances include evaluating if economic data has been manipulated (Gonzales‐Garcia & Pastor, 2009 ; Nye & Moul, 2007 ; Rauch et al, 2011 , etc.) and assessing the veracity of information from household surveys (González, 2020 ; Judge & Schechter, 2009 ; Villas‐Boas et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Both the Chi‐square test and KS test can present type I error in large samples, and therefore their compliance with Benford's law is circumspect in scenarios where we reduce the difference in the proportions (Barney & Schulzke, 2016 ; Druică et al, 2018 ; González, 2020 ). To alleviate this concern, we use the mean average deviation to check the concordance of the frequency distribution with Benford's law.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the literature review, it can be concluded that Mean Absolute Deviation (hereinafter referred to as MAD) is a standard method of examining the fit of distributions. MAD is commonly used to assess distribution fit (González, 2020;Isaković-Kaplan, Demirović, & Proho, 2021;Nigrini, 2012). This method examines the mean value of the absolute differences between the empirical and Benford's distributions for the analysed digits.…”
Section: Research Methods and Samplementioning
confidence: 99%